1990
DOI: 10.1083/jcb.110.4.871
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear exchange of the U1 and U2 snRNP-specific proteins.

Abstract: Abstract. The snRNP particles include a set of common core snRNP proteins and snRNP specific proteins. In rodent cells the common core proteins are the B, D, D', E, F and G proteins in a suggested stoichiometry of BzD'2D2EFG. The additional U1-and U2-specific proteins are the 70-kD, A and C proteins and the £ and B" proteins, respectively. Previous cell fractionation and kinetic analysis demonstrated the snRNP core proteins are stored in the cytoplasm in large partially assembled snRNA-free intermediates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 51 publications
2
8
0
1
Order By: Relevance
“…they are transported separately from the rest of the snRNP (20). The study in Xenopus laevis oocytes confirmed that U1A is targeted to the nucleus independently of its association with snRNA (21).…”
supporting
confidence: 52%
“…they are transported separately from the rest of the snRNP (20). The study in Xenopus laevis oocytes confirmed that U1A is targeted to the nucleus independently of its association with snRNA (21).…”
supporting
confidence: 52%
“…The indications that A' protein may exchange into snRNPs as presented here and previously (10) and that A' may mediate protein-protein interactions within U2 snRNP suggests that U2 snRNPs are dynamic particles whose functions might be modulated by the presence of A' protein.…”
Section: Resultsmentioning
confidence: 96%
“…The two largest U1-specific proteins, U1-70K and U1-A, bind directly to the U1 snRNA while the U1-C protein is attached through protein-protein interactions with U1-70K and Sm proteins (Nelissen et al 1994). U1-A and U1-C are imported to the nucleus independently of the U1 snRNA (Jantsch and Gall 1992;Kambach and Mattaj 1992), indicating that U1 snRNP assembly occurs in the nucleus (Feeney and Zieve 1990). The role of CBs in this process is not clear.…”
Section: U1 Snrnpmentioning
confidence: 97%